The effect of lipid metabolism regulator anthocyanins from Aronia melanocarpa on 3T3-L1 preadipocytes and C57BL/6 mice via activating AMPK signaling and gut microbiota. Issue 14 (11th June 2021) - Chen, Chunping; Yang, Ximing; Liu, Siqi; Zhang, Mingyan; Wang, Chao; Xia, Xinxiu; Lou, Yuhang; Xu, Hongyan
Abstract : The effect of lipid metabolism regulator AAM on 3T3-L1 preadipocytes and mice via activating AMPK signaling and gut microbiota. Abstract : This study investigated lipid metabolism regulation by anthocyanins from Aronia melanocarpa (AAM) in 3T3-L1 preadipocytes and high fat diet (HFD) mice. Ultra-performance liquid chromatography/ion mobility quadrupole time-of-flight mass spectrometry analysis identified the constituents of AAM, which decreased lipid content and inflammation in 3T3-L1 cells without cytotoxicity. Meanwhile, taking normal diet and orlistat mice as references, AAM supplementation improved blood lipid levels and adipocyte degeneration, promoted beneficial gut microbial growth, and maintained lipid metabolism in HFD mice. Furthermore, AAM activated the AMP-activated protein kinase (AMPK) signaling pathway, accompanied by the regulation of adipogenic transcription factors and their target genes in vitro and in vivo. Collectively, our data demonstrated that AAM exhibits anti-adipogenic activities that were partially mediated by the AMPK pathway and gut microbiota regulation. This study provides new insight into the regulation of lipid metabolism by AAM and suggests that AAM has potential therapeutic effects on hyperlipidemia.